The Maritime Turn in EU Foreign and Security Policies - Riddervold, Marianne. author. aut Link
VIII, 240 p.
Keywords: This book provides the first substantial treatment of the maritime security policies of the European Union. The findings add to the literature on EU foreign policy by a comparative, theoretically informed analysis of EU maritime security policies across three cases: the development of the EU’s Maritime Security Strategy and action plan (EUMSS); EU Arctic policies; and EU anti-piracy mission Atalanta. Focusing on the aims, actors and mechanisms of integration in these cases, the book speaks to all three main discussions in the literature on EU foreign policy, including the extent to which it has moved beyond intergovernmental cooperation; whether or not EU foreign and security policy has a particular normative dimension that makes it different from foreign policy as it is conventionally understood and, interlinked; how we can explain its emergence and characteristics. By focusing on maritime security policies the book also adds to the international relations literature more broadly. .